Opening the “Can of Worms”: Preparing Teachers to Address Issues Relating to “Race” - Davies, Jane (Frontiers in Education, 2021)
This paper reports the findings of a study which involved a critical examination of “race”-related provision on initial teacher education (ITE) programmes in England. It draws upon data collected as part of a national survey of ITE provision which included interviews with providers and students, and case studies of ITE providing institutions. The study utilized aspects of Critical Race Theory and Critical Whiteness Studies as a theoretical framework with which to analyse the data. The paper explores the nature of provision relating to “race,” suggesting that teacher educators and student teachers are often ill-equipped to address the complexities relating to this area and, as a result, they can fail to recognize the importance and potential impact of their professional practice, and their pedagogical decisions. It suggests that ITE practices are often underpinned by dysconscious racisms and manifestations of Whiteness, leading to a marginalization of “race” input, with opportunities for deeper interrogation missed, or actively avoided. The paper explores some of the constraints impacting on ITE namely a lack of time; a lack of confidence on the part of a predominantly White teacher educator workforce; a lack of recognition of the importance and significance of “race” on the part of White student teachers, and an emphasis of superficial measures of student satisfaction at the expense of deeper interrogation and deconstruction of hegemonic norms. It makes recommendations relating to how practice can be improved within the current challenging global contexts in relation to “race” equality. It calls for teacher education to aspire to produce novice teachers willing and prepared to embrace “race”-related challenges in their teaching careers, and to contribute to curricula which acknowledge and address inequality.